حماية الحقوق الثّقافية في زمن الحرب والنّزاعات المسلّحة - خلف, بوبكر (جامعة الوادي University of Eloued, 2015)
كثرت الحروب والنزاعات المسلّحة في وقتنا الحاضر، خاصّة بعد الثورات الإجتماعية التي اجتاحت البلدان العربية وما أفرزته من آثار سلبية على مجتمعاتنا وأفرادها، ومن مساس خطير بحقوق الإنسان جملة وبالحقوق الثقافية تفصيلا، وخاصّة التراث الثقافي الذي يعدّ ملكا للإنسانيّة جمعاء، ولهذا لابدّ من تفعيل المسؤوليّة الدوليّة وتحميلها الجهات المخلّة بأحكام القانون الدولي الإنساني سواء كانت الدّول، أو الحكومات، والتّنظيمات، والأفراد، ناهيك عن توقيع العقوبات الدوليّة التي قد تتدرج من التنديد إلى العقوبات الإقتصادية وصولا إلى الجزاءات العسكريّة. Abstract: Nowadays, wars and armed conflicts have increased especially after the social uprisings that devastated most Arab countries, causing a lot of negative effects upon social and individual levels, as well as severe harms to the human rights as a whole, and to cultural standards in detail particularly to the cultural heritage which is entirely human property, it is therefore as an absolute necessity to urge on the whole world responsibility in order to charge the deficient quarters with the international law disposition whether it be states Governments communities or individuals, and to apply gradual sanction from the strong objections to the effective economic sanctions and even to the military interventions.
Keywords: الحقوق الثقافيّة؛ النزاعات المسلّحة؛ الثورات الإجتماعيّة؛ القانون الدولي الإنساني؛ العقوبات الدوليّة؛ حقوق الإنسان